Gene expression of selected apoptotic markers in human oral squamous carcinoma HSC-3 cell line treated with Myrmecodia pendans plant extract - Lestari, Widya; Yusry, Wan N A W; Iskandar, Siti H; Ichwan, Solachuddin J A; Irfan, Nining I; Suriyah, Wastuti H (Makara Journal of Health Research, 2019)
Background: Myrmecodia pendans (M. pendans), or Sarang Semut, is an epiphyte with anticancer potential. It was recently reported that it induces apoptotic activity in the human oral squamous carcinoma (HSC-3) cell line. This study aimed to investigate the effect of M. pendans treated samples on the expression of apoptotic markers, Bax and Bcl-2. Methods: M. pendans was purchased from West Papua, Indonesia. The hypocotyl was dried thoroughly and then extracted aqueously. The apoptotic activity was detected via flow cytometry. Bax and Bcl-2 expression was analyzed by quantitative real-time polymerase chain reaction. Results: Results of our cell cycle analysis reveal that aqueous extract of M. pendans induced apoptosis in 2.5 and 5 mg/mL but no change between these two concentrations. Apoptosis was observed at 24 h but not at 48 h. Bax and Bcl-2 expression in HSC-3 cells was affected by M. pendans. At 24 h, upregulation of Bax was observed at 2.5 mg/mL. However, after 48 h, Bax expression showed no changes at any concentration. Bcl-2 was significantly downregulated after 48 h of treatment. Conclusions: M. pendans extract induced apoptosis in HSC-3 cells, which might occur via the proapoptotic (Bax) and antiapoptotic (Bcl-2) pathways